Review of the Caribbean Agricultural Research and Development Institute (CARDI) : final report - Roach, Keith...[et al] ([s.n.] [S.l.], 2000)
Seeks to determine whether CARDI's strategies, policies, programmes and projects: respond to national agricultural policies and plans of Member States; are efficiently and effectively conducted and managed; represent the critical core activities that are in scope and level operations commensurate with the financial contributions of the Member States; and maintain and enhance the quality and impact of the Institute.